Synthesis of some acylated 2-pyrazoline and chalcone derivatives - Coskun, Demet; Ahmedzade, Misir (Springer, 2014)
alpha-Haloesters containing the chalcone structure and alpha-haloamides containing the pyrazoline ring have been synthesized by reaction of substituted hydroxy chalcones and pyrazoline derivatives (prepared as reported elsewhere; J Chem 8(4):1574-1581, 2011) with chloroacetyl chloride in dry THF in the presence of Et3N. The structures of the synthesized compounds were confirmed by IR, H-1 NMR, and (for some compounds) C-13 NMR spectroscopy.
Keywords: Aromatic aldehydes; Chalcones; Pyrazolines; Benzofurans; alpha-Haloamides; alpha-Haloesters